Impending atypical femoral fractures associated with bisphosphonates: postoperative diagnosis after hip prosthesis. Clinical cases presentation. - Bottai, Vanna; Piolanti, Nicola; Digrandi, Giuseppe; Menconi, Agnese; Antognetti, Damiano; Di Lonardo, Michele; Scaglione, Michelangelo; Raffaetà, Gloria (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Number of hip prosthesis implants in arthritis, number of patients treated with bisphosphonates to prevent fragility fractures and, together, number of atypical femoral fracture’s cases are increasing. Case series: This article describes two cases of hip arthritis, treated with hip replacement, in patients using bisphosphonates for a long time; in both cases an incomplete atypical femoral fracture was misdiagnosed before the surgery. Authors describe the importance to carry out a complete osteometabolic and radiographic pre-operative examination of patients in treatment with bisphosphonates going to hip replacement, to check the possible presence of incomplete atypical femoral fracture and to optimize surgical and pharmacological treatment. Conclusions: In hip prosthesis surgery, prior diagnosis of incomplete atypical femoral fractures can indicate the choice of a different kind of prosthesis stem to optimize surgical results. This can also positively impact to rehabilitation in term of duration and daily activities recovery.